1983
DOI: 10.1111/j.1365-2125.1983.tb01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in drug free fraction during alcohol withdrawal.

Abstract: 1 Free fractions of diazepam, propranolol and warfarin were determined in 15 male chronic alcoholics in alcohol withdrawal. 2 On admission the mean free fraction of diazepam was 25% above and propranolol 44% below the limits of normal range, while the mean warfarin free fraction was in high normal range. One week later mean free fraction of diazepam declined by 20% while propranolol and warfarin increased by 24% and 19% respectively (P < 0.05).3 Propranolol free fraction and a,-AGP concentrations were highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…Our results of higher propranolol concentrations at the onset of AW than after the resolution of AW symptoms are in line with those of Sandor et al [30], who found elevated levels in concentrations of free propranolol in plasma during withdrawal syndrome. Another factor may be related to changes in hepatic blood flow or in the metabolism of the drug during the first passage through the liver.…”
Section: Discussionsupporting
confidence: 82%
“…Our results of higher propranolol concentrations at the onset of AW than after the resolution of AW symptoms are in line with those of Sandor et al [30], who found elevated levels in concentrations of free propranolol in plasma during withdrawal syndrome. Another factor may be related to changes in hepatic blood flow or in the metabolism of the drug during the first passage through the liver.…”
Section: Discussionsupporting
confidence: 82%
“…An increase in the free fraction of thiopentone was observed in patients with alcoholic cirrhosis (Pandele et al, 1983). An increase in the free fatty acids in alcoholic patients may displace acidic drugs from their binding to albumin (Sandor et al, 1983). In the present study, the plasma protein binding of thiopentone was not studied.…”
Section: Discussionmentioning
confidence: 69%
“…Total concentrations of propranolol were higher during withdrawal than after resolution of the withdrawal symptoms (Kähkönen, 2003), but concentrations of unbound fraction of propranolol were opposite (Sandor et al, 1983).…”
Section: Discussionmentioning
confidence: 97%